Medicinal Plants of Tehrathum District, Eastern Nepal - Rai, Mani Bahadur (Our Nature, 2006)
Vaidhya (Herbalist) use the medicinal plants to remove the ailments since time immemorial. Tehrathum district is found rich in medicinal plants. A total of 105 vascular plants were recorded to be used in different diseases. Information was collected by discussion through local communities and field observations. Some plants were found to be used in different diseases in different places. The indigenous knowledge is transferring from generation to generation in certain families without any written records. Keyword:s Medicinal Plants, NTFPs, Tehrathum, Shaman doi:10.3126/on.v1i1.304 Our Nature (2003) 1: 42-48